2002
DOI: 10.1258/13576330260440736
|View full text |Cite
|
Sign up to set email alerts
|

Child development services: A multidisciplinary approach to professional education via videoconference

Abstract: summary We have piloted a monthly series of multidisciplinary case discussions via videoconference in the area of child development. The project provided a forum for clinical discussion of complex cases, peer review, professional development and networking for allied health professionals and paediatricians. Six sites in Queensland participated in the project; each site presented at least one case for discussion. The videoconferences ran for 90 min each and were attended by an average of 26 health professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Audits conducted by Australian health departments cite education and administration as the principal reasons for VC usage. 6 Teaching hospitals should be a source of specialized knowledge that permits the shared care of patients throughout the region (state and/or territory). [9][10][11] In Queensland, a range of education programmes are conducted routinely for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Audits conducted by Australian health departments cite education and administration as the principal reasons for VC usage. 6 Teaching hospitals should be a source of specialized knowledge that permits the shared care of patients throughout the region (state and/or territory). [9][10][11] In Queensland, a range of education programmes are conducted routinely for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Nelson R Mandela School of Medicine at the University of KwaZulu-Natal has increased the psychiatry registrar posts three-fold over the last three decades.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…Randomized, controlled trials have shown that videoconference classes can be effective in medical education. 29 Several [30][31][32] but not all 33 reports have suggested that videoconference-delivered education is satisfactory to clinicians. However, little research has evaluated whether educational outreach can be effectively provided via videoconference.…”
Section: Introductionmentioning
confidence: 99%